Analogie bei Thomas von Aquin: Onto-epistemische, semantische und sprachlogische Probleme - Spune, Valentina (Verlag Karl Alber, 2023)
The concept of analogy, which today again comes into focus of contemporary debates, had been extensively and in manifold ways discussed in the Latin scholasticism. In this study, Aquinas’ use of this concept – against the background and in context of these discussions – is reconstructed in epistemological, ontological and logical-semantic terms. The explanation of the connection modes of this use in all three areas is at the heart of the present analytical study. The author explains step by step this connection using the key terms like similitudo, assimilatio, proportionalitatis, participatio and unitas.